Otitis media diagnosis model for tympanic membrane images processed in two-stage processing blocks - Basaran, Erdal; Comert, Zafer; Celik, Yuksel; Budak, Umit; Sengur, Abdulkasdir (Iop Publishing Ltd, 2020)
[Abstract Not Available]
Keywords: Intelligent Fault-Diagnosis; Feature-Selection; Otoscopy Simulator; Neural-Networks; Classification; Children; System